National geniuses’ heritage as potential for the development of cultural tourism in Romania - Nicolaie, Daniela; Matei, Elena; Cooley, Timothy John; Vijulie, Iuliana; Cushing, David; Truțescu, Marius Nicolae (Acta geographica Slovenica, 2023)
This article investigates how domestic tourists perceive the possibilities of boosting cultural heritage tourism in Romania, through the capitalization of national genius personalities. The methodology is based on the survey method. The research identified 22 geniuses, largely represented in national culture, and acknowledged and demanded by the market. The vast majority have been converted into tourist attractions, however those of international visibility are missing or are underrepresented in Romanian heritage tourism. An increased focus on geniuses would be highly valued by tourists and could reinforce the value of cultural heritage, consequently, boosting tourism resources. This would lead to multiple and sustainable benefits for destinations’ development, but certain infrastructure and management gaps would need to be filled.